Atomic Carbon Layers Supported Pt Nanoparticles for Minimized CO Poisoning and Maximized Methanol Oxidation. Issue 38 (28th July 2019) - Bai, Gailing; Liu, Chang; Gao, Zhe; Lu, Baoying; Tong, Xili; Guo, Xiangyun; Yang, Nianjun
Abstract: Maximizing activity of Pt catalysts toward methanol oxidation reaction (MOR) together with minimized poisoning of adsorbed CO during MOR still remains a big challenge. In the present work, uniform and well‐distributed Pt nanoparticles (NPs) grown on an atomic carbon layer, that is in situ formed by means of dry‐etching of silicon carbide nanoparticles (SiC NPs) with CCl4 gas, are explored as potential catalysts for MOR. Significantly, as‐synthesized catalysts exhibit remarkably higher MOR catalytic activity (e.g., 647.63 mA mg −1 at a peak potential of 0.85 V vs RHE) and much improved anti‐CO poisoning ability than the commercial Pt/C catalysts, Pt/carbon nanotubes, and Pt/graphene catalysts. Moreover, the amount of expensive Pt is a few times lower than that of the commercial and reported catalyst systems. As confirmed from density functional theory (DFT) calculations and X‐ray absorption fine structure (XAFS) measurements, such high performance is due to reduced adsorption energy of CO on the Pt NPs and an increased amount of adsorbed energy OH species that remove adsorbed CO fast and efficiently. Therefore, these catalysts can be utilized for the development of large‐scale and industry‐orientated direct methanol fuel cells. Abstract : Atomic carbon layer coated silicon carbide nanoparticles (SiC NPs) are utilized to anchor uniform and well‐distributed Pt catalysts where minimized CO poisoning and maximum methanol oxidation ability are realized. This originates from reduced CO adsorption energy on Pt sites and an increased amount of OH species during methanol oxidation, due to the fast electron transfer process from Pt to SiC.